Water quality and antibiotic resistance at beaches of the Galápagos Islands - Overbey, Katie N.; Hatcher, Sarah M.; Stewart, Jill R. (Frontiers in Environmental Science, 2015)
Tourism and residential population growth are increasing on the Galápagos Islands, yet the effects of this growth on environmental quality are not well understood. The goal of this study was to characterize recreational water quality on one of the inhabited islands of the Galápagos (Isla San Cristóbal). Five beaches were sampled to allow a comparison between beaches with and without discharge of human sewage, and to help elucidate the effects of human activities in this unique environment. Enterococcus concentrations were quantified using IDEXX Enterolert® and antibiotic resistance testing was performed on Escherichia coli isolated by membrane filtration. All study beaches sometimes exceeded international guidelines for recreational water quality, and significantly higher Enterococcus concentrations were found near sites subjected to sewage discharge (p < 0.01). These sewage-impacted sites also had higher levels of antibiotic resistant E. coli, suggesting that human activities are increasing the levels of resistance that would occur naturally. Future studies should characterize the extent of this impact both spatially and temporally. The results of this study demonstrate that sewage can contribute antibiotic resistant bacteria to marine waters and suggest that human impacts in the Galápagos Islands extend to the environmental resistome. This impact is likely common in areas across the globe wherever tourists frequently carry and use antibiotics.